Cybersecurity of Robotic Systems: Leading Challenges and Robotic System Design Methodology - Vibekananda Dutta (MDPI AG, 2021)
Recent years have seen a rapid development of the Internet of Things (IoT) and the growth of autonomous robotic applications which are using network communications. Accordingly, an increasing advancement of intelligent devices with wireless sensors (that means autonomous robotic platforms) operating in challenging environments makes robots a tangible reality in the near future. Unfortunately, as a result of technical development, security problems emerge, especially when considering human–robot collaboration. Two abnormalities often compromise the basic security of collaborative robotic fleets: (a) Information faults and (b) system failures. This paper attempts to describe the methodology of a control framework design for secure robotic systems aided by the Internet of Things. The suggested concept represents a control system structure using blocks as the components. The structure is designed for the robots expected to interact with humans safely and act connected by communication channels. The properties of the components and relations between them are briefly described. The novelty of the proposed concept concerns the security mechanisms. The paper also categorizes two different modes of network attacks summarizing their causal effects on the human–robot collaboration systems. The issue of standardization is also raised. In particular, the works of the National Institute of Standards and Technology (NIST) and European Parliament (EP) on the security templates for communication channels are commented.